2008
DOI: 10.1111/j.1748-1716.2008.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of left ventricular hypertrophy and aortic remodelling in NO‐deficient hypertensive rats: effect of l‐arginine and spironolactone

Abstract: In our study, the reversion of hypertension and LVH was not dependent on the restoration of NO-synthase activity. Moreover, LV fibrosis and aortic remodelling seem to be more resistant to conditions resulting in regression of LVH. Preserved level of fibrosis in the initial period of LVH regression might result in loss of structural homogeneity and possible functional alterations of the LV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…In the present study we observed that aortic remodeling in L-NAME hypertension was characterized by increased aortic WT similarly to our previous studies. 25 The wall thickening was accompanied by reduced ID, slightly increased aortic cross-sectional area, and most importantly increased WT/ID ratio in accordance with previous studies on this model of hypertension. 27,48 In our study we have investigated the effects of the AT 2 R agonist on PWV in L-NAME rats.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the present study we observed that aortic remodeling in L-NAME hypertension was characterized by increased aortic WT similarly to our previous studies. 25 The wall thickening was accompanied by reduced ID, slightly increased aortic cross-sectional area, and most importantly increased WT/ID ratio in accordance with previous studies on this model of hypertension. 27,48 In our study we have investigated the effects of the AT 2 R agonist on PWV in L-NAME rats.…”
Section: Discussionsupporting
confidence: 78%
“…The effect of L-NAME administration on BP was reported in numerous studies by our laboratory [31][32][33] and others. 22,23,26 L-NAME-induced hypertension is associated with target organ damage, such as cardiac hypertrophy and fibrosis, 33 vascular remodeling, 25 and endothelial damage. 26 Current European guidelines also regard augmented PWV as an indicator of subclinical organ damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, TERalb was higher in atherosclerotic patients, however, was not different between normotensive and hypertensive subjects (Pedrinelli et al 1998). In contrast, another study demonstrated that endothelial permeability was higher in hypertensive subjects, but endothelium-dependent relaxation was not different in uncomplicated mild to moderate hypertension (Paulis et al 2008). We also found that reversal of hypertension did not alter endothelial permeability.…”
Section: Discussionsupporting
confidence: 55%
“…Further study is needed to fully elucidate the pathways involved. However, several circulating factors, including asymmetric dimethyl arginine (35,36), parathyroid hormone (37), aldosterone (38), fibroblast growth factor-23 (39), angiotensin-2 (40), endogenous cardiac glycosides (41), vitamin D (42), and circulating angiogenesis inhibitors, have been implicated (35).…”
Section: Pathophysiology Of Arrhythmia In Ckdmentioning
confidence: 99%